1993
DOI: 10.1093/treephys/13.3.275
|View full text |Cite
|
Sign up to set email alerts
|

Influence of photoperiod and temperature on frost hardiness and free amino acid concentrations in black spruce seedlings

Abstract: We investigated the effects of a 4-week exposure to an 8-h or 18-h photoperiod at 5 or 25 degrees C on the development of hardiness to -20 degrees C and the accumulation of proline (Pro), arginine (Arg) and tryptophan (Trp) in shoots of black spruce (Picea mariana (Mill.) B.S.P.) seedlings. The greatest degree of hardening to -20 degrees C occurred in seedlings exposed to an 8-h photoperiod at 25 degrees C, and some hardening occurred in seedlings exposed to 5 degrees C in either an 8-h or 18-h photoperiod. Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 23 publications
2
20
0
Order By: Relevance
“…We observed a progressive but significant accumulation of arginine in stems and roots, with a surge occurring by mid-August. Our results showed that a transition seems to occur in nitrogen metabolism when natural day length approaches 14 h. Odlum et al (1993) concluded that the accumulation of arginine in black spruce shoot was likely induced by exposure to short days. The surge of arginine was of higher amplitude in small trees, indicating differential arginine metabolism between growth phenotypes.…”
Section: White Spruce Growthmentioning
confidence: 49%
See 1 more Smart Citation
“…We observed a progressive but significant accumulation of arginine in stems and roots, with a surge occurring by mid-August. Our results showed that a transition seems to occur in nitrogen metabolism when natural day length approaches 14 h. Odlum et al (1993) concluded that the accumulation of arginine in black spruce shoot was likely induced by exposure to short days. The surge of arginine was of higher amplitude in small trees, indicating differential arginine metabolism between growth phenotypes.…”
Section: White Spruce Growthmentioning
confidence: 49%
“…Later in the autumn, arginine was incorporated into newly synthesized proteins in the buds. Considering the photoperiodic control of bud set, it is noteworthy that short day length also induces the accumulation of arginine in shoots of black spruce (Picea mariana) (Odlum et al 1993) and of soluble storage proteins in bark of poplar (Populus sp.) species (Coleman et al 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Lowtemperature stress influences the metabolism of nitrogenous compounds, in particular certain amino acids and polyamine compounds (Mazzucotelli et al 2006;Davey et al 2009). For instance in several plant species it was shown that proline accumulates in response to cold stress (Yelenosky 1979;Jouve et al 1993;Odlum et al 1993). Several genes involved in signal transduction were found to be differentially expressed.…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed that acclimatization to cold or freezing temperatures in plants is not dependent on the synthesis of new compounds but rather on the transient accumulation of certain compounds, including N-containing compounds such as amino acids or proteins [67]. In conifers, some amino acids, such as tryptophan and proline, have been identified as osmolite solutes that exert cryoprotectant functions during cold acclimatization [65,68,69]. The use of tryptophan in these plants is extremely interesting because its synthesis is linked to the secondary metabolism, which is especially well developed in conifers.…”
Section: Abiotic Interactionsmentioning
confidence: 99%
“…For example, γ-aminobutiric acid (GABA) has a possible role in stress acclimatization acting as a signaling metabolite [64]. Conversely, although conifers exhibit seasonal changes in the arginine levels [68], the role of arginine in acclimatization to cold and freezing temperature appears to be related to the production of polyamines [68]. Additionally, other N metabolites, such as glycine betaine can act as cryoprotectants [67]; however, the role of glycine betaine has not been completely elucidated.…”
Section: Abiotic Interactionsmentioning
confidence: 99%